Contemporary themes in strategic people management a case-based approach - Hall, David; Pilbeam, Stephen; Corbridge, Marjorie (Palgrave Macmillan, 2013)
Examines core contemporary topics in HRM using case studies to highlight theory and provide students with a business context within which to understand the topic. Questions help students to critically evaluate the material and reflect on alternative approaches. Ideal for undergraduate, postgraduate and MBA students.